Nurita nilasari bunga kharisma RESIKO PERSALINAN KALA I FASE AKTIF MEMANJANG TERHADAP KEJADIAN ASFIKSIA PADA BAYI BARU LAHIR DI RUMAH SAKIT MUHAMMADIYAH SITI KHODIJAH KABUPATEN KEDIRI - nilasari, nurita (Judika (Jurnal Nusantara Medika), 2018)
The research was based on the high risk of the active phase of labor first stage extends to the incidence of asphyxia in newborns at Muhammadiyah Hospital Siti Khodijah Kediri regency in 2017. The research method used in analytical comparison with the case-control approach. This study aims to identify and analyze the risk of first stage labor and lengthening the active phase of asphyxia. A result that may result from the high incidence of birth asphyxia caused by lengthening the active phase of the first stage is the high maternal mortality rate (MMR) and infant mortality rate (IMR). With a population of 56 asphyxiated newborn (cases) and 56 normal newborns (controls) at the Muhammadiyah Hospital Siti Khodijah Kediri in 2017 that totaled 112 babies. Large sample of 56 asphyxiated newborns (cases) and 56 normal newborns (controls) samples taken by sampling saturated samples. How to measure a variable by using a sheet of data collectors. The value of each subject is collected from data collection sheets are summed in the form of numbers and percentages. Based on the data processing is known that maternal active phase with the first stage extends memili 0,92 greater risk of having infant with birth asphyxia compared to mother with active phase I stage of labor is not lengthened. By calculating the value of Oods Ratio (OR) and 95% CI 0,4-1,9.